The economic impact of Covid-19 - Hudd, Emily (Core library guide to Covid-19, 2021)
Many of the world's largest economies shut down almost overnight as nations tried to slow the spread of COVID-19. These measures saved lives, but they also cost millions of jobs and shuttered many companies-some temporarily, others forever. The Economic Impact of COVID-19 studies how the pandemic and the fight against it affected every part of the economy, from individuals to huge corporations.